Market and State: The Perspective of Constitutional Political Economy - Viktor J. Vanberg (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2004)
The paper approaches the "market versus state" issue from the perspective of constitutional political economy, a research program that has been advanced as a principal alternative to traditional welfare economics and its perspective on the relation between market and state. Constitutional political economy looks at market and state as different kinds of social arenas in which people may realize mutual gains from voluntary exchange and cooperation. The working properties of these arenas depend on their respective constitutions, i.e. the rules of the game that define the constraints under which individuals are allowed, in either arena, to pursue their interests. It is argued that "improving" markets means to adopt and to maintain an economic constitution that enhances consumer sovereignty, and that "improvement" in the political arena means to adopt and to maintain constitutional rules that enhance citizen sovereignty.
Keywords: D60; H10; 330; Economics of rules; welfare economics; constitution of markets; constitution of politics; Marktwirtschaft; Staatliche Einflussnahme; Verfassungsökonomik; Theorie